Biopsychospiritual Approach Using Combined Murottal Therapy and Silver Dressing for Pain and Second-Degree Burns Wounds: A Case Study - Siti Fauziah; Hasniatisari Harun; Eka Afrima Sari (Multidisciplinary Journals, 2026)
Second-degree burns are tissue injuries that cause disruption of skin integrity, severe pain, and a high risk of infection. Burn management requires adequate wound care and effective pain control. Silver sulfadiazine dressings function as antimicrobial agents to prevent infection, while Qur’anic murottal therapy serves as auditory distraction to reduce pain perception through relaxation mechanisms and decreased physiological stress responses. This case study aims to describe the combination of murottal therapy and silver dressing in pain management and wound care for a second-degree burn using a biopsychospiritual approach in a patient with 22.5% TBSA second-degree burns on days 7 to 10 of treatment. Interventions included daily wound care with topical silver sulfadiazine and sterile dressings, as well as murottal therapy of Surah Ar-Rahman for approximately 15 minutes before, during, and 30 minutes after wound care. Evaluation was conducted using the Bates-Jensen Wound Assessment Tool (BWAT) and Numeric Rating Scale (NRS) over four days. The results showed that the wound was in the early proliferative phase with a stable BWAT score of 27 and no signs of secondary infection. Pain scores decreased gradually throughout the intervention, with an average reduction of two points after each session, accompanied by increased relaxation and comfort following wound care. The combination of silver dressing and murottal therapy in this case helped control pain and supported the wound healing process both physiologically and psychologically.